Otomatisasi Pencatatan Akuntansi Sederhana untuk Usaha Mikro Kecil dan Menengah (UMKM) (Studi kasus ECO 21 Purwokerto) - Puspa Mudi Widianti; Riny Jefri (Jurnal Humanipreneur, 2023)
This research was conducted using the Participation Action Reseach (PAR) methode, the data obtained is primary data in the form of interviews with the owner. The results and discussion of this study are the application of the Accounting Recording System in MSMEs still uses a manual system which result in incomplete and inaccurate financial report result. In the research, the creation and implementation of an accounting recording system based on Microsoft Excel was carried out. This system shows that the process of recording accounting becomes easier, this is useful so that later business owners get better and more acuurate financial information. It is also useful for managing funds, evaluating business performance, and making decisions in the future.